Cohabitation of red swamp crayfish (Procambarus clarkii) and Pacific white shrimp (Litopenaeus vannamei) cultured in low salinity water - Jesse James; Sunni Dahl; David Teichert-Coddington; Anita M. Kelly; James D. Creel; Benjamin H. Beck; Ian A.E. Butts; Luke A. Roy (Aquaculture Reports, 2024)
Culture of Pacific white shrimp (Litopenaeus vannamei) and red swamp crayfish (Procambarus clarkii), using an intercropping production strategy, is being used by one shrimp farmer in Alabama. A concern is that crayfish feed on invertebrates. This raises the question of whether crayfish would feed on shrimp, negatively impacting survival and production. Two trials were conducted using different systems to investigate the cohabitation of these species. Trial 1 consisted of a 24-tank clear water system. Treatment 1 served as an experimental control and consisted of 20 shrimp fed a daily ration of shrimp feed. Treatment 2 comprised of 20 shrimp and one adult crayfish per tank, each receiving a calculated daily ration of shrimp feed. Treatment 3 had the same number of shrimp and crayfish as above, but no additional shrimp feed was added to account for the crayfish in the tank. Trial 2 used a green water on-levee flow-through tank system, stocked at an initial mean shrimp stocking weight of 0.15 ± 0.01 g with four replicates and similar treatments as Trial 1. Shrimp survival was 91.9 % when they were reared in a clear water system without crayfish. Adding crayfish significantly decreased shrimp survival, with no difference in survival between crayfish treatments fed a daily crayfish ration (58.8 %) and those not receiving a daily crayfish ration (40.6 %). Shrimp weight gain did not differ between treatments. However, when shrimp were in the presence of crayfish not receiving a daily crayfish ration, tank-to-tank variability in weight gain by >50 % compared to other treatments increased. Shrimp survival was 92.0–97.3% across treatments when reared in a green water system (Trial 2) without crayfish. Results indicate that cohabitation of crayfish and shrimp is feasible.